2020
DOI: 10.1111/rda.13840
|View full text |Cite
|
Sign up to set email alerts
|

A study on stress response and fertility parameters in phenotypically thermotolerant and thermosensitive dairy cows during summer heat stress

Abstract: It is well documented that heat stress (HS) causes subfertility in dairy cows. However, during the last ten years we have been observing that, under high temperature-humidity index (THI ≥ 75), despite the overall reduced fertility, some cows conceive at the first artificial insemination (AI). Here, we examined distinctive features of cows with conserved fertility under severe HS. From the databases of three herds, 167 lactating Holstein cows were selected; group TT cows (n = 57) conceived in the previous summe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…In this study, we describe for the first time structural and haemodynamic differences in the gravid uterus and the CL of pregnancy that were associated with a long exposure of cows to elevated ambient temperatures. In a previous study, we have shown that despite the cooling methods used, cortisol and heat shock protein 70 (HSP70) concentrations are elevated during the hot months of the year (Nanas et al., 2020). In the present study, neither the dry matter intake was affected (results not shown) nor the body temperature exceeded the normal range of the breed, confirming our previous findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we describe for the first time structural and haemodynamic differences in the gravid uterus and the CL of pregnancy that were associated with a long exposure of cows to elevated ambient temperatures. In a previous study, we have shown that despite the cooling methods used, cortisol and heat shock protein 70 (HSP70) concentrations are elevated during the hot months of the year (Nanas et al., 2020). In the present study, neither the dry matter intake was affected (results not shown) nor the body temperature exceeded the normal range of the breed, confirming our previous findings.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of cortisol and progesterone concentrations were carried out by ELISA, according to the manufacturers’ recommendations as previously described (Nanas et al. 2020). The samples were analysed in duplicate; when differences exceeded 10%, the samples were re‐analysed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the experiment, the maturation medium was modified with the addition of 5 ng/mL HSP70. The HSP70 dose was selected on the basis of HSP70 concentration that we measured in the peripheral blood of 164 heat stressed dairy cows [ 29 ]. COCs ( n = 1933) were randomly allocated to 1 of 4 maturation protocols: 39 °C for 24 h without (group C39, n = 471) or with HSP70 (group H39, n = 353), for 6 h at 41 °C (from the 2nd to 8th hour of IVM) followed by 16 h at 39 °C in the presence (group H41, n = 704) or in the absence of HSP70 (group C41, n = 405).…”
Section: Methodsmentioning
confidence: 99%
“…During summer months despite the overall suppression in conception rates, and the increased embryo losses, a proportion cows remain extremely fertile conceiving at the first A.I. (Nanas et al., 2020). We have examined the difference of some characteristics between summer and winter early pregnancies, and we found that during the summer, the pregnancy associated glycoproteins (PAGs) concentrations are higher than those of the winter (Nanas et al., 2021).…”
Section: Discussionmentioning
confidence: 99%